Proceedings of the 17th ACM Conference on International Computing Education Research 2021
DOI: 10.1145/3446871.3469748
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sense of Belonging and Student Outcomes in CS1 and Beyond

Abstract: Students' sense of belonging has been found to be connected to student retention in higher education. In computing education, prior studies suggest that a hostile culture and a feeling of nonbelonging can lead women, Black, Latinx, Native American, and Pacific Islander students to drop out of the computing field at a disproportionately high rate. Yet, we know relatively little about how computing students' sense of belonging presents and evolves (if at all) through their college courses, particularly in course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…1,2,15−18,27,29−32 For example, in both introductory math and computer science courses, studies have shown that women have a lower sense of belonging than men, and this sense of belonging is correlated to performance and motivation in the course. 15,18 Additionally, in both algebrabased and calculus-based introductory physics courses, women have a lower sense of belonging than men even though the percent of women in algebra-based introductory physics is above 50%. 16,27,32 A student's belonging uncertainty has been less studied.…”
Section: Social Belonging In General Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,15−18,27,29−32 For example, in both introductory math and computer science courses, studies have shown that women have a lower sense of belonging than men, and this sense of belonging is correlated to performance and motivation in the course. 15,18 Additionally, in both algebrabased and calculus-based introductory physics courses, women have a lower sense of belonging than men even though the percent of women in algebra-based introductory physics is above 50%. 16,27,32 A student's belonging uncertainty has been less studied.…”
Section: Social Belonging In General Chemistrymentioning
confidence: 99%
“…It has repeatedly been observed across a variety of contexts that women report a lower sense of belonging and a higher belonging uncertainty than men in introductory STEM courses, including online courses. ,, ,, For example, in both introductory math and computer science courses, studies have shown that women have a lower sense of belonging than men, and this sense of belonging is correlated to performance and motivation in the course. , Additionally, in both algebra-based and calculus-based introductory physics courses, women have a lower sense of belonging than men even though the percent of women in algebra-based introductory physics is above 50%. ,, A student’s belonging uncertainty has been less studied. In an introductory computer science course, it was seen that women had a higher belonging uncertainty than men and that higher uncertainty was correlated with their perceived potential ability .…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach to teaching foundational science courses does not adequately equip students to become scientists and science learners (Ellery, 2018). In addition, the traditional didactic approach also has the potential to alienate students and strip them of their sense of belonging (Krause-Levy, et al, 2021). While many of the knower dispositions of scientists and science learners could be taught effectively using Emergency Remote Teaching, some were more challenging to teach, and for students to learn.…”
Section: Discussionmentioning
confidence: 99%
“…These tasks were deliberately designed to be relevant to the global context in which all academics and students found themselves during 2020/2021. By being contextually relevant, DMP also hoped to make the content more interesting and engaging for the students and begin to inculcate a sense of belonging which he hoped would ultimately foster improved academic success (Krause-Levy, et al, 2021). His efforts appeared to have the desired effect i.e., the regulative discourse appears to be enabling epistemic access to the instructional discourse, with several students noting:…”
Section: Specifically Students Commentedmentioning
confidence: 99%
“…Within engineering, social belonging (i.e., acceptance and membership) has been positively and significantly linked with grade performance in introductory engineering classes (Schar et al, 2017). And for computer science students, lower (in‐class) belonging, which includes elements of acceptance, membership, and support, has been linked to poorer academic outcomes, whether measured by course pass rate (Krause‐Levy et al, 2021) or a specific post‐course content assessment (Moudgalya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%